Implementasi Budaya Mutu di TK Negeri Pembina Kabupaten Semarang - Maslihah, Nur Isna; Miyono, Noor (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Kindergarten is an educational institution that is very important in shaping the character of students. Kindergartens that have a good quality culture will be able to produce quality students. The purpose of this research is to determine the implementation of supervision management and quality culture in the Pembina State Kindergarten, Semarang Regency. The results of this research show: (1) quality culture planning involving the principal, deputy principal, teacher council, employees, committee, parents/guardians of students, and several community leaders. (2) organizing a quality culture is achieved by dividing and delegating work systems according to their respective fields. (3) the implementation of a quality culture is carried out using exemplary principles and cooperative cooperation with several stakeholders. (4) supervision management of the Semarang Regency Pembina State Kindergarten is carried out collaboratively. The results of the implementation of school quality culture management in the Pembina State Kindergarten, Semarang Regency, are the achievements achieved by the school in both academic and non-academic fields.